WeForest uses, and enables staff to apply, a WLE/ICRAF impact evaluation tool for holistic planning in the restoration of forest landscapes considering synergies, tradeoffs and uncertainties in Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
After WLE/ICRAF trained the monitoring and evaluation expert of WeForest in the use of a stochastic impact evaluation tool it had developed to predict outcomes of livelihood and landscape restoration, WeForest changed its approach to project design. The organization now undertakes ex-ante analyses that consider risks and uncertainties for all its Ethiopian restoration projects, and, together with WLE/ICRAF, has further developed a technical guide on the use of the tool in restoration projects generally.